Добробут домогосподарств в сільській місцевості в системі цілей економічної політики регіону - Почерніна, Наталя Вікторівна; Почернина, Наталья Викторовна; Pochernina, Natalia (Люкс, 2018)
UK: Проаналізовані окремі показники якості життя сільських домогосподарств Запорізької області. Виявлені основні дестабілізуючі фактори добробуту сільських домогосподарств регіону. Визначені пріоритети регіональної економічної політики в агарній сфері. Запропонована схема узгодження стратегічних цілей соціального-економічної політики регіону до 2030 року з Цілями сталого розвитку, адаптованими для України. EN: The regional development strategy to 2030 and the regional plan for the agrarian sector and rural areas development should include a scheme for coordinating the objectives of regional economic policy with the sustainable development goals. This scheme separates the goals of region sustainable development into three groups: priority goals; Goals related to the priority and social goals based on the two previous ones. The priority objectives are: Eradicate poverty, Decent work, Reduce inequality, Sustainable development of cities and communities.
Households' well-being in rural area in the system of regional economic policy goals
Keywords: сільські домогосподарства; добробут; регіон; цілі сталого розвитку; економічна політика; аграрний сектор; rural household; well-being; region; Sustainable Development goals; economic policy; agrarian sector